2021
DOI: 10.1186/s13063-021-05398-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and diagnostic accuracy of Telephone Administration of an adapted wound heaLing QuestiONnaire for assessment for surgical site infection following abdominal surgery in low and middle-income countries (TALON): protocol for a study within a trial (SWAT)

Abstract: Background Surgical site infection is the most common complication of abdominal surgery, with a global impact on patients and health systems. There are no tools to identify wound infection that are validated for use in the global setting. The overall aim of the study described in this protocol is to evaluate the feasibility and validity of a remote, digital pathway for wound assessment after hospital discharge for patients in low- and middle-income countries (LMICs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The study protocol was pre-registered online on the MRC Hubs for Trial Methodology Research SWAT store database 16 (Queen’s University Belfast) (SWAT ID 126) and published in Trials 17 . This report was prepared with reference to the Statistical Analyses and Methods in the Published Literature (‘SAMPL’) guidelines 18 , the methodology standards of the Patient-Centred Outcomes Research Institute (‘PCORI’) 19 , the STARD guidelines for diagnostic test accuracy studies 20 , and the COSMIN guidelines for patient-reported outcomes research 21 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol was pre-registered online on the MRC Hubs for Trial Methodology Research SWAT store database 16 (Queen’s University Belfast) (SWAT ID 126) and published in Trials 17 . This report was prepared with reference to the Statistical Analyses and Methods in the Published Literature (‘SAMPL’) guidelines 18 , the methodology standards of the Patient-Centred Outcomes Research Institute (‘PCORI’) 19 , the STARD guidelines for diagnostic test accuracy studies 20 , and the COSMIN guidelines for patient-reported outcomes research 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The index diagnostic test under evaluation was a telephone-administered Bluebelle WHQ 17 , adapted for use in LMICs. The WHQ was originally developed and validated in the UK (English language) to assess post-discharge infections after abdominal surgery 22 , 23 .…”
Section: Methodsmentioning
confidence: 99%
“…A universal outcome reporter “Bluebelle” Wound Healing Questionnaire has demonstrated promise as tool for remote detection of SSI, demonstrating excellent discrimination and reliability 45 , 46 ; however, this has only undergone evaluation in a single language in one country, and cultural and linguistic adaptation and validation to support international application. 47 No included studies used videography to help identify SSI; this may prove a useful adjunct to future development in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Seventh, we were unable to differentiate here between different methods of remote wound assessment (ie, telephone vs video), although from ongoing work across our network it is likely that a majority of assessment would have been telephone-based. 47 Eight, the cohort study used a pragmatic observation methodology and did not standardize training or delivery of telemedicine. This should therefore be interpreted as the real-world effectiveness of telemedicine, rather than the potential efficacy of telemedicine in an optimized system.…”
Section: Discussionmentioning
confidence: 99%
“…0 = No fluid leaking 10 = Constantly leaking Pain from wound, pain related to dressing changes, fluid leakage from dressing, bleeding, smell, itching Patient No Acute and chronic wounds in a wound cleansing trial [ 31 ] Wound Management Questionnaire (Elliott et al) [ 6 ] In the past 24 h, has fluid leaked through the dressing? Not at all, A little, Quite a bit, A lot Dressing replacement in the last 24 h Patient No Surgical sites [ 32 ] Drainage severity, assessed by provider National Wound Assessment Form [ 7 ] Wound moisture level Dry, Moist, Wet, Saturated, Leaking HCP No NA World Union of Wound Healing Societies’ Initiative Exudate Assessment (WUWHS) [ 8 ] Dry Wound bed is dry; no visible moisture and primary dressing is unmarked; dressing may be adherent to wound Moist Small amounts of fluid are visible when the dressing is removed; primary dressing may be lightly marked; dressing change frequency appropriate for dressing type Wet Small amounts of fluid are visible when the dressing is removed; the primary dressing is extensively marked, but strikethrough is not occurring; dressing change frequency is appropriate for dressing type Saturated Primary dressing is wet, and strikethrough is occurring; dressing change is required more frequently than usual for the dressing type; peri-wound skin may be macerated Leaking Dressings are saturated and exudate is escaping from primary and secondary dressings onto clothes or beyond; dressing change is required much more frequently than usual for dressing type Exudate color, consistency, odor (see “Drainage appearance” below) HCP No NA; referenced in treatment consensus for epidermolysis bulla [ 33 ] and chronic wound management [ 34 ] New Wound Bed Score (WBS) [ 9 ] 0–2 0 = Severe 1 = Moderate 2 = None/Mild Edg...…”
Section: Qualitative Wound Drainage Toolsmentioning
confidence: 99%